The character of consciousness - Chalmers, David John, 1966- (New York ; Oxford : Oxford University Press, 2010)
What is consciousness? How does the subjective character of consciousness fit into an objective world? How can there be a science of consciousness? Here, Chalmers develops a unified framework that addresses these questions and many others.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Consciousness